Living Qur’an dan Etika Ekologis: Puasa Ramadan sebagai Praksis Keagamaan Kesadaran Lingkungan di Pedesaan Indonesia - Fauzan Fahmi; Husnel Anwar Matondang (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This article examines Ramadan fasting as a lived Qur’anic praxis that shapes ecological ethics within a rural Muslim community in Indonesia. Focusing on Bandar Labuhan Village, the study employs a qualitative approach grounded in Living Qur’an methodology to explore how Qur’anic values are embodied through everyday religious practices. Data were collected through in-depth interviews, participant observation, and documentation during the month of Ramadan. The findings reveal that fasting functions as a form of embodied moral discipline that reorganizes patterns of consumption, resource use, and social interaction. Practices of self-restraint, moderation, and communal assistance cultivated during Ramadan contribute to reduced waste, mindful energy use, and shared responsibility for environmental resources, even in the absence of explicit ecological discourse. This study argues that Ramadan fasting produces an ecological habitus—a set of durable dispositions that orient individuals and communities toward sufficiency and care in human–environment relations. By integrating Islamic ecological ethics with Living Qur’an studies, this article demonstrates that the Qur’an lives not only through recitation and ritual symbolism but also through ecological practices embedded in religious routines. The study contributes to broader discussions on religion and ecology by highlighting the ethical potential of Islamic ritual practices in addressing contemporary environmental challenges.